Pengembangan Sistem Informasi Budidaya Perikanan (Studi Kasus Pada Dinas Ketahanan Pangan dan Perikanan Kabupaten Bireuen) - Abid Alfath; Widhy Hayuhardhika Nugraha Putra; Welly Purnomo (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
Food and Fisheries Agency or Dinas Ketahanan Pangan dan Perikanan (DKPP) of Bireuen regency is a regional government institution that has functions regarding the implementation and public services for the availability of food distribution and aquaculture in the Bireuen regency area. In implementing its business functions, DKPP periodically carries out the aquaculture data by conducting field observations to share the information towards the public and other relevant stakeholder. However, the data collection process is still implemented manually so it is not efficient yet because it requires a lot of time, moreover the DKPP does not have a data center so that documents are stored in seperated storage locations. In addition, there are still problems in the fish disease reporting activities because the integrated fish health post (Posikandu) is only located in one location so that it has not been able to reach the entire Bireuen regency. Therefore, it is necessary to have an information system which overcomes this problem. The information system that will be developed is website-based using the Laravel framework. The method used in developing the system is the waterfall model. Further, the system is tested using validation testing, compatibility testing and User Acceptance Test (UAT) methods. The test results showed that the functions in the system are valid, the system can run compatible on various types of browsers and from the results of the UAT it is found that the system is accepted by the user.